2013
DOI: 10.1103/physrevb.88.144108
|View full text |Cite
|
Sign up to set email alerts
|

Shock-induced phase transformations in gallium single crystals by atomistic methods

Abstract: Utilizing a modified embedded atom method potential, we performed large-scale classical molecular dynamics simulations (with up to 50 million atoms) to investigate the response of Ga single crystals to shock compression along the three major orientations of the orthorhombic A11 ground state, i.e., [001], [010], and [100]. For weak shocks with particle velocity u p < 300 m/s, these defect-free single crystals respond elastically, but for stronger shocks, they undergo a structural phase transformation and then (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 40 publications
2
5
0
Order By: Relevance
“…The present study builds on this previous work by reporting simulations where both the convergence of supercell and k-point grid sizes were investigated, and by simulations performed along the principal Hugoniot up to a pressure of 150 GPa. We find that the calculated Hugoniot is in very good agreement with both the experimental data [11] and recent classical molecular dynamics calculations [18,19] performed using a Modified Embedded Atom Method (MEAM)…”
supporting
confidence: 81%
“…The present study builds on this previous work by reporting simulations where both the convergence of supercell and k-point grid sizes were investigated, and by simulations performed along the principal Hugoniot up to a pressure of 150 GPa. We find that the calculated Hugoniot is in very good agreement with both the experimental data [11] and recent classical molecular dynamics calculations [18,19] performed using a Modified Embedded Atom Method (MEAM)…”
supporting
confidence: 81%
“…[1][2][3][4][5][6][7][24][25][26] Elementary gallium is another interesting substance that shares some common features with water, e.g., having multisolid phases and negatively sloped melting line. [28][29][30][31][32][33][34] Tien et al 35 observed two separate peaks at 260 K and 220 K in the nuclear magnetic resonance (NMR) spectra of opal-confined gallium which is interpreted as the existence of two liquid gallium phases confined in opal. Using computer simulations, Jara et al 36 reported that gallium has two states of liquid, a) Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, MD simulations and experimental studies have been performed to explore solid-solid phase transformations in single crystals [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. For example, Kadau et al [24] identified the role of shockwave strength on structural transformations in Ga single crystals. Cui et al [21] explored the role of nanovoid size on the BCC to HCP phase transformation in Fe during shock.…”
Section: Introductionmentioning
confidence: 99%